Oropharyngeal candidiasis and Candida colonization in HIV positive patients in northern India - Vijeta Maurya; Ashutosh Srivastava; Jyoti Mishra; Rajni Gaind; Rungmei S.K. Marak; Anil Kumar Tripathi; Mastan Singh; Vimala Venkatesh (Journal of Infection in Developing Countries)
Introduction: Oropharyngeal candidiasis (OPC) is the most common opportunistic fungal infection reported in human immunodeficiency virus (HIV) positive patients worldwide. This prospective study was undertaken to investigate OPC and Candida colonization (CC) and their correlation with CD4+ cell counts and antiretroviral therapy (ART) in HIV-positive patients.